2020
DOI: 10.3390/catal10090964
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photocatalytic Degradation of Caffeine Using Titanium Dioxide Photocatalyst Immobilized on Circular Glass Sheets under Ultraviolet C Irradiation

Abstract: This work presents the development of titanium dioxide (TiO2) film immobilized on circular glass sheets for photocatalytic degradation of caffeine under ultraviolet C (UVC) irradiation. TiO2 was synthesized through the ultrasonic-assisted sol–gel method and immobilized on circular glass sheets by the doctor blade technique. Polyvinylpyrrolidone (PVP) was used to mix with the TiO2 precursor solution to enhance film adhesion on the glass surface. TiO2 film was mainly composed of anatase phase with a small amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 49 publications
2
4
0
Order By: Relevance
“…The k values obtained in this study coincide with the results observed by others (Chuang et al 2011;Luna et al 2018;Mai et al 2018;Sacco et al 2018;Ghosh et al 2019;Muangmora et al 2020). Table 2 shows comparisons of the pseudo-first-order rate constants.…”
Section: Effect Of Initial Caf Concentration On Its Removal and Kineticssupporting
confidence: 89%
See 1 more Smart Citation
“…The k values obtained in this study coincide with the results observed by others (Chuang et al 2011;Luna et al 2018;Mai et al 2018;Sacco et al 2018;Ghosh et al 2019;Muangmora et al 2020). Table 2 shows comparisons of the pseudo-first-order rate constants.…”
Section: Effect Of Initial Caf Concentration On Its Removal and Kineticssupporting
confidence: 89%
“…•À (Mozia 2010;Laohaprapanon et al 2015;Puga 2016). The (Sudha & Sivakumar 2015;Ahmad et al 2016;Awfa et al 2018;Pathakoti et al 2018), TiO 2 had attracted many researchers and been found successful due to its easy availability, low cost, non-toxicity, chemical and thermal stability, and applicability to solar energy (Bouarioua & Zerdaoui 2017;Rimoldi et al 2017;Muangmora et al 2020;Sujatha et al 2020). As far as is known, no study has been conducted on CAF degradation using intermittent UV irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…The drop in caffeine concentration occurred at different rates. The corresponding initial rate constants were calculated by the following formula, assuming a first-order reaction 54 where C is the caffeine concentration at time t and C 0 is the initial caffeine concentration. 55 The results in Table 3 revealed that the 30 μm sample exhibited the best photocatalytic activity by far, followed by the 100 and 200 μm samples, while the 50 μm sample showed the least activity.…”
Section: Resultsmentioning
confidence: 99%
“…Equation (1) was also applied to calculate the degree of mineralization (DOM) using the carbon concentrations from TOC measurements. In addition, a pseudo-first-order (1st) kinetic model (Equation (2)) was used to determine the reaction rate constant (k 1st ) from the ln (c t /c 0 ) vs. t plot [ 31 ]. …”
Section: Methodsmentioning
confidence: 99%